GAYA KEPEMIMPINAN PEREMPUAN DI KEMENTERIAN AGAMA - Noor Efni Salam, Nurmi, Seno Andri, (Jurnal Ilmu Administrasi Negara, 2019)
Women’s Leadership Style in the Ministry of Religion. This study aims to analyze the style of women’s leadership in the ministry of religion in the city of Pekanbaru. This study uses a qualitative descriptive research method approach. Data collection techniques using questionnaires, interviews, and observations. Research informants were the Head of the Ministry of Religion Office. Head of Subdivision, Head of Sharia Organizing Section, and ASN Staff. Data analysis in this study used interactive model analysis from Miles and Huberman which included: the stages of data reduction, data presentation, and data verification to draw conclusions. The results of the study can be concluded that the leadership of women in the Ministry of Religion in Pekanbaru is more dominant using participatory leadership styles. Although the leadership sometimes leaders combine other leadership styles and also use the theory of situations in the application of leading a position.